Pengaruh Harga Dan Promosi Terhadap Keputusan Penggunaan Jasa Aplikasi Maxim - Robin, Robin; Sofyan, Silvia; Kevin, Kevin (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The objective of this research is to examine the impact of pricing and promotion on service use choices within the context of Maxim, serving as a case study for students majoring in STMB Multismart Management. The used research methodology is characterized by a quantitative approach. The research methodology used in this study is descriptive quantitative research, which aims to provide a comprehensive analysis of the subject matter. Additionally, the nature of this research is explanatory, as it seeks to elucidate the underlying factors and relationships associated with the observed phenomena. The population consists of students enrolled in the management major at STMB MULTISMART. The investigation used a basic random sampling approach. The sample size in this research consisted of 54 students. In order to assess the validity and reliability of the test, a sample of 54 consumers was selected from the whole population under consideration. The findings indicate that the impact of price on service utilization decisions is not statistically significant, while promotion has a partial effect on service utilization for Maxim. The coefficient of determination, which is 0.284 or 28.4%, suggests that the combined influence of price and promotion in explaining customer satisfaction is 28.4%. The remaining 71.6% of the variance may be attributed to factors outside the variables under investigation, such as user convenience, safety, and other relevant variables.